Inside Cover: Optimized Synthesis of Solution‐Processable Crystalline Poly(Triazine Imide) with Minimized Defects for OLED Application (Angew. Chem. Int. Ed. 3/2022). Issue 3 (29th December 2021) - Burmeister, David; Tran, Ha Anh; Müller, Johannes; Guerrini, Michele; Cocchi, Caterina; Plaickner, Julian; Kochovski, Zdravko; List‐Kratochvil, Emil J. W.; Bojdys, Michael J.
Abstract : Poly(triazine imide) is a member of the family of graphitic carbon nitrides and its graphitic morphology allows exfoliation of the material into thin, solution‐processable layers, while at the same time reducing migration and drift of chemically bonded dopants. A team of researchers from King's College London, Humboldt‐Universität zu Berlin, Carl von Ossietzky Universität Oldenburg, and Helmholtz‐Zentrum Berlin (HZB) constructed the first thin layer, organic light emitting device (OLED) with a solution‐processed graphitic organic material as a metal‐free emission layer. For details see the Research Article by Michael J. Bojdys et al. (e202111749 ).